2016
DOI: 10.1103/physrevlett.116.025501
|View full text |Cite
|
Sign up to set email alerts
|

Two Dimensional Ice from First Principles: Structures and Phase Transitions

Abstract: Despite relevance to disparate areas such as cloud microphysics and tribology, major gaps in the understanding of the structures and phase transitions of low-dimensional water ice remain. Here, we report a first principles study of confined 2D ice as a function of pressure. We find that at ambient pressure hexagonal and pentagonal monolayer structures are the two lowest enthalpy phases identified. Upon mild compression, the pentagonal structure becomes the most stable and persists up to ∼2  GPa, at which point… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
190
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(210 citation statements)
references
References 58 publications
17
190
0
3
Order By: Relevance
“…3,[14][15] Theoretical investigations of the structures of the two-dimensional (2D) water confined in between the flat walls have suggested puckered rhombic monolayer ice, planar hexagonal, or amorphous phases depending on the conditions and models employed in the simulations. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Although the structures of confined water have been predicted for a variety of dimensions and materials using molecular dynamics (MD) simulations, the first experimental observation of the 2D water in between the two graphene sheets was obtained very recently using high-resolution transmission electron microscopy measurements (TEM). 30 This observation revealed the formation of a monolayer of planar "square" ice with a high packing density and, depending on the inter-graphene distance, the formation of bi-and trilayer crystallites of water.…”
Section: Introductionmentioning
confidence: 99%
“…3,[14][15] Theoretical investigations of the structures of the two-dimensional (2D) water confined in between the flat walls have suggested puckered rhombic monolayer ice, planar hexagonal, or amorphous phases depending on the conditions and models employed in the simulations. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Although the structures of confined water have been predicted for a variety of dimensions and materials using molecular dynamics (MD) simulations, the first experimental observation of the 2D water in between the two graphene sheets was obtained very recently using high-resolution transmission electron microscopy measurements (TEM). 30 This observation revealed the formation of a monolayer of planar "square" ice with a high packing density and, depending on the inter-graphene distance, the formation of bi-and trilayer crystallites of water.…”
Section: Introductionmentioning
confidence: 99%
“…However, these experiments have been questioned [2], with it even being suggested that it is sodium chloride contamination and not ice that is responsible for the square symmetry observed. So far, it is not clear under what conditions (if any) square ice is stable.Theoretical investigations of the stability of confined 2D ice at high lateral pressures can, in principle, help in disentangling this issue and in complementing experimental findings [3][4][5][6][7][8][9][10]. From a theoretical perspective, the prediction of square 2D ice can be traced back to Nagle's 1970's "unit model" of ice [3].…”
mentioning
confidence: 99%
“…However, later atomistic force field (FF) simulations found that 2D ice prefers a buckled rhombic structure [4,5]. More recently, density functional theory (DFT) based investigations [6][7][8][9] have been performed. However, these have produced qualitatively different results depending on the precise details of the calculations and, in particular, on the choice of exchange-correlation (XC) functional.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one can concentrate searches on particular space groups that have been found by experiment or previous searches to be common in certain types of structure, such as in inorganic or organic crystals. 83 Structure searching is also very flexible and can readily be adapted for discovering point defect structures, 84,85 surface and interface structures, [86][87][88] etc. The most important aspects of searching are illustrated in Fig.…”
Section: Importance Of Finding the Correct Structurementioning
confidence: 99%